Political Law Interpretation on President’s Refusal to Sign an Approved Bill with the House of Representatives - Fernando Hasiholan Manalu; Retno Saraswati; Devi Yulida (Faculty of Law, Universitas Jenderal Soedirman, 2023)
Signing by the President is one of the stages in the formation of a law. The constitutional facts show that the President has several times not signed draft a bill that has been mutually agreed upon. The author is interested in discussing: The practice of the President not signing draft laws that have been approved with the House of Representatives. Second; political law interpretation on the President's actions not sign for draft law that is agreed with the House of Representatives. This paper uses a normative juridical approach with a statutory and conceptual approach and is then analyzed deductively. The results obtained are that several laws were passed without the President's approval, which are then analyzed from grammatical, historical, comparative, structural and theological interpretations. On this issue, the authors suggest that there be an agreement in the persona of the President, as well as the President's clear reasons for refusing to sign the bill.Keywords: Bills; House of Representatives; Presidents; Signing by the President